PENGARUH KUALITAS PRODUK DAN HARGA TERHADAP PENGHASILAN PETANI GULA AREN DI DESA TAMBELANG KECAMATAN TOULUAAN SELATAN KABUPATEN MINAHASA TENGGARA - Laloan , Cherys F.; Tiwow, Gilly; Mangangantung , Aprilia (Literacy: Jurnal Pendidikan Ekonomi, 2025)
This study aims to analyze the influence of Product Quality and Price on the Income of palm sugar farmers in Tambelang Village, South Touluaan District, Southeast Minahasa Regency. This research uses a quantitative approach. The analysis results show that Product Quality (X1) has a significant partial effect on Farmers' Income (Y), with a significance value of 0.007 (<0.05). Price (X2) also has a significant effect on Farmers' Income, with a significance value of 0.013 (<0.05). In addition, the simultaneous test results indicate that both independent variables together influence Farmers' Income, with an F significance value of 0.001 (<0.05). Therefore, it can be concluded that Product Quality and Price have a significant effect, both partially and simultaneously, on Farmers' Income. This research is expected to serve as a reference for farmers in developing effective product quality to increase their income. Keywords: Product Quality, Price, Farmers' Income